(untitled) (SAARC Journal of Agriculture, 2022)
Experiment was conducted at the Agricultural Farm of Patuakhali Science and Technology University to know the morphological characteristics of different mutants of mungbean and to find out tolerant/least susceptible mutant(s) against flea beetle, aphid and pod borer based on the reaction of insect pests to promising mutants of mungbean during the period from April to June, 2015. The mutant MBM-07(S)-2 was found to be the tallest (32.57 cm) with highest number of branches/plant (5.03), highest number of leaves/plant (11.06) among all mutants and check variety while MBM-07-Y-2 (23.40 cm) was the shortest plant height, MBM-656-51-2 had the lowest number of branches/plant (3.73), MBM-347-13 (7.03) had the lowest number of leaves/plant. The mutant MBM-427-87-3 had the highest number of pods (5.00) compared to other mutants but MBM-656-51-2 had the lowest number of pods/plant (3.09). Significantly the highest pod length and the highest number of seeds/pod were recorded in the mutant MBM-07-Y-1 (6.37 cm) while the lowest pod length (5.19 cm) was in MBM-80(LCAL) and lowest number of seeds/pod was in the mutant MBM-390-94-Y (5.34). Mutant MBM-347-13 had the lowest population of flea beetle (18.00) and pod borer (2.00) compared to all other mutants while the lowest number of aphid/plant was observed in mutant MBM-07-Y-1 (1.00). In case of infestation, the mutant MBM-347-13 had the lowest percentage of infestation (20.69%) by flea beetle, (3.18%) by pod borer but the lowest infestation by aphid (3.33%) was recorded in the mutant MBM-390-94-Y while the mutant MBM-427-87-3 had the highest percentage of plant infestation (37.80%) by flea beetle, pod damage (9.69%) by pod borer and variety BARI moog-6 had the highest percentage (34.45%) of plant infestation by aphid. Mutant MBM-347-13 was least susceptible to flea beetle and pod borer while mutant MBM-427-87-3 was highly susceptible to flea beetle and pod borer. However, mutant MBM-390-94-Yand MBM-07-Y-2 were less susceptible to aphid while BARI moog-6 and mutant MBM-427-87-3 were highly susceptible to aphid. SAARC J. Agric., 20(1): 97-106 (2022)